Implementation of the Minangkabau Culture Curriculum at Kindergarten - Warmansyah, Jhoni; Yuningsih, Restu; Sari, Meliana; Urrahmah, Nisa; Data, Mulya Rahman; Idris, T (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2022)
The existence of elements of the implementation of Minangkabau culture that became a peculiarity of the curriculum in Padang Panjang Jihad Mosque Kindergarten is interesting to be studied more deeply. Therefore, this study aims to analyze the implementation of the Minangkabau cultural curriculum related to the planning, implementation, and evaluation of learning. Qualitative research type of descriptive method. Data collection techniques on research objects are carried out through observation, interview, and observation. Data analysis starts from data reduction, presentation of data, and concluding. Assurance of data validity using data triangulation techniques. As a result of the research, curriculum planning is carried out by integrating national curriculum of 2013, PAI Curriculum, and Minangkabau cultural context. The implementation of the implementation curriculum is evident from the Daily Learning Implementation Plan (RPPH), which is integrated into the learning load. Performance, assignment (project), and observation in assessing special activities of Minangkabau culture that has become the habituation of children, especially in kato nan ampek, sumbang nan duo baleh and the art of Minangkabau tradition